Variability in end-tidal PCO2 and blood gas values in humans. - Crosby, A; Robbins, P (2003)
The aims of this study were: (1) to determine the within-subject, between-day variability in end-tidal P(CO2) (P(ET,CO2)); (2) to determine whether the within-subject, between-day variability in P(ET,CO2) was caused by variations in metabolic acid-base status; and (3) to determine whether between-subject variations in blood gas variables arose predominantly through variations in respiratory or renal pH control mechanisms. Fourteen healthy males were studied, of whom 12 provided adequate data for further analysis. Each subject was studied on at least six different occasions, with each visit separated by at least 1 week. On each occasion, P(ET,CO2) was determined over a 4-10 min period using a fine nasal catheter taped just inside the nose, and an arterialised capillary blood sample was obtained from each ear and analysed for blood gases. The following results were obtained. (1) P(ET,CO2) showed a standard deviation (S.D.) for the within-subject, between-day variation of 1.06 mmHg. (2) Less than 5% (P = NS) of the variability in P(ET,CO2) could be explained by underlying variations in metabolic acid-base status. (3) The variation in blood gas values between individuals did not fit a pattern associated with either a predominantly respiratory or a predominantly renal origin. Furthermore, the pattern of variation in the blood gas data suggested that variations in the renal controller for pH and the respiratory controller for pH were not independent. The precise origins of variability in blood gas regulation remain obscure.